Penggunaan Video Animasi Berbasis 3D Gaya Kartun Untuk Meningkatkan Pemahaman Lima Sila Pancasila Pada Siswa Sekolah Dasar Tahun 2025 - Indah Mutia Hafsari Lubis; Mawar Sari; Hafidzah Al Fira Hafsah Limbong; Nadila Nasfati Hamdah; Bella Sadilla; Masitah; Annisa Hidayah; Nayla Khairani; Adha Rizky Rahman Panjaitan (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Civics education in elementary schools still faces various challenges, particularly in delivering learning materials that tend to be theoretical and less engaging for students. As a result, students’ understanding of the meaning and application of the five principles of Pancasila remains limited. This study aims to improve students’ learning comprehension of the five principles of Pancasila through the use of 3D cartoon-style animated videos as learning media. This research employed a Classroom Action Research (CAR) method conducted in two cycles. The results indicate that the use of 3D cartoon-style animated videos effectively enhances students’ understanding of the five principles of Pancasila. Improvements were observed in students’ comprehension scores and learning participation from the first cycle to the second cycle. Therefore, 3D animated video media can serve as an effective alternative learning tool to improve elementary school students’ understanding of Pancasila values.